Effectiveness of the GASING Method in Improving Numeracy Skills in Indonesia’s Frontier Region - Fransiska Carolin Mayabubun; Nandi Nandi; Lili Somantri; Fransiska Carolin Mayabubun; Nandi (Universitas Negeri Malang, 2026)
Indonesia’s frontier, outermost, and disadvantaged regions face persistent educational disparities, particularly in foundational numeracy. This study examines the effectiveness of the GASING (Gampang, Asyik, dan Menyenangkan-Easy, Fun, and Enjoyable) method in enhancing numeracy skills among teachers (n=32) and students (n=64) in Manggarai Barat Regency, East Nusa Tenggara Province, Indonesia. Situated within the geography of education framework, this research employs a pre-experimental one-group pre-test and post-test design across five numeracy domains: foundational number sense (Bakal Kubagi), addition, multiplication, subtraction, and division. The intervention was implemented over 17 days as part of the Gejur Rekeng Le program. Results demonstrate substantial score gains across all domains for both groups. Teachers exhibited mean gains ranging from +18.8 to +66.6, while students showed gains from +45.3 to +75.6. The highest absolute gains were observed where pre-test baselines were lowest, particularly in division and foundational number sense. These findings suggest that the GASING method is a viable pedagogical intervention for addressing numeracy deficits in geographically marginalized regions, with implications for educational equity policy in Indonesia’s archipelagic context.